Skull and brain gunshot wound during the armed conflict in eastern Ukraine. Report 1. Clinical, functional and structural features - Sirko, Andriy (Ukrainian Neurosurgical Journal, 2015)
Purpose. To study features skull and brain of gunshot wounds (SBGW) in local fighting in the East of Ukraine. Material and methods. The results of complex examination and treatment of 790 injured persons been treated in Mechnikov Dnipropetrovsk Regional Clinical Hospital from May 25 to December 31, 2014. SBGW were diagnosed in 64 (8.1%) patients, that was 18.8% in a structure of all closed and open head injuries, 33.5% — of all gunshot wounds of different areas of the head, 63.4% — of gunshot wounds of soft tissues of different areas of the skull. Results. SBGW mostly (in 90.6% of cases) were due to fragments of mine-explosive devices. Penetrating wounds with dura mater injury dominate (in 64.1%) among SBGW. Ricochet wounds were most common (in 50%) among SBGW in local fighting. High frequency of brain injury was due to secondary injury by skull bones fragments. In addition to traumatic brain injuries, widespread use of mine-explosive devices causes frequent occurrence (in 65.6%cases) of combined injuries of several organs and systems of the body. Conclusions. Multiple wounds caused by fragments of explosive devices that affect several anatomical sites are the most common type of combat traumas.